Total Synthesis of Natural Terpenoids Enabled by Cobalt Catalysis - Xiao, Shu; Ai, Likun; Liu, Qichang; Yang, Baihui; Huang, Jian; Xue, Wei; Chen, Yang (Frontiers in Chemistry, 2022)
Transition metal catalysis plays an essential role in the total synthesis of natural products. Cobalt-mediated asymmetric catalysis has successfully been used as a primary or a secondary step in the total synthesis of natural products, especially terpenoids. Terpenoids represent one of the most prominent families among various categories of natural products, attracting immense attention due to their promising physiological activities. This review summarizes the recent advances toward the total synthesis of terpenoids by cobalt-mediated asymmetric catalysis, which may shed some light on their future synthetic efforts toward natural pesticides such as celanguline, azadirachtin, etc.